Aerial Shells with the Aspect of Wounding Potential - Durdu, Murat; Cantürk, Nergis (The Bulletin of Legal Medicine, 2017)
Objective: Aerial shells -a sample of pyrotechnics- are produced for recreational purposes. Because of materials used in construction and design, they consist some potential risks. Besides, there is a risk of utilization of shells as a simple weapon system and utilization of energetic ingredients in home-made bombs. Occasionally some news have been seen about woundings and deaths related to aerial shells. With this perspective, our study aimed to research wounding potential of shells.    Materials and methods: Four experiments were held including; physical examination of locally produced batteries, observation of battery functioning, expelling and detonation of shells, speed and blast pressure measurement utilizing a fastcam and pressure sensors. In physical examinations it is identified that, batteries are constructed in form of a cylindirical-cardboard-made barrels packed together, fired with short time intervals with a time fuse attached to barrels. Shells are configured with some powder/solid form of pyrotechnic mixtures added with little amount of earth and grains.Results: Upon expelling of shells, intensive white-color smoke observed and 40,2 cm lenght (SD=7,21) flame eruption measured. In 0.5 m distance from barrels, 28 g-weight-shells (SD: 3,8) speed calculated as 52,61 m/s (SD: 6,92). Approximately 144,42 cm (SD: 36,61) diameter flame ball and fragmentations were identified, 89,09 kPa (SD: 16,62) detonation pressure value calculated.Conclusion: Considering all findings, due to the pyrotechnic mixtures in their desings, their speed, flame eruption from barrels, fireball formation and fragmentation effects, it is evaluated that aerial shells have potential wounding risk.
Keywords: Pyrotechnics; aerial shells; wounding